Results of V.M. Boltinsky research of century development in the context of national tractor industry development - Кривоконь, Олександр Григорович (Eastern-European Journal of Enterprise Technologies, 2012)
The article briefly reviewed biography and scientific activity of V.M. Boltinskyi, his writings and teachings. The significance of these studies for the development of modern tractor industry is shown. The contribution of V.M. Boltinskyi in scientific and pedagogical foundations of Engineering is described